A Duterte Reader: Critical Essays on Rodrigo Duterte's Early Presidency, edited by Nicole Curato - Barbaza, Remmon E. (Archīum Ateneo, 2024)
A Duterte Reader: Critical Essays on Rodrigo Duterte's Early Presidency, edited by Nicole Curato